STRUCTURAL ORGANIZATION OF MODERN MEMORY SCHEMES (Transport systems and technologies, 2018)
The first time the new multi-memory scheme that removed restrictions on the known components triggers. These schemes have lower costs of equipment for one memory status and have an open structure and the ability to change a subset of states that are unable to perform trigger existing components and have a matrix structure storing conditions. In addition, it operates in continuous time automaton has an open structure, reduce hardwarecosts to a storage condition at 33%; increased functionality (due rekonfiguriruemaya subsets in a matrix structure storage conditions), making restructuring of storing conditions. In addition, BFSP have high reliability (minimum 50%) and vitality that is important for use in the construction compa p’yuternyh of such important facilities as nuclear plants, air and rail transportation, aerospace, which much important for the security of any country.
Keywords: Multi-circuit memory trigger.